Molecular mechanisms of Saccharomyces cerevisiae stress adaptation and programmed cell death in response to acetic acid - Giannattasio, Sergio; Guaragnella, Nicoletta; Ždralević, Maša; Marra, Ersilia (Frontiers in Microbiology, 2013)
Beyond its classical biotechnological applications such as food and beverage production or as a cell factory, the yeast Saccharomyces cerevisiae is a valuable model organism to study fundamental mechanisms of cell response to stressful environmental changes. Acetic acid is a physiological product of yeast fermentation and it is a well-known food preservative due to its antimicrobial action. Acetic acid has recently been shown to cause yeast cell death and aging. Here we shall focus on the molecular mechanisms of S. cerevisiae stress adaptation and programmed cell death in response to acetic acid. We shall elaborate on the intracellular signaling pathways involved in the cross-talk of pro-survival and pro-death pathways underlying the importance of understanding fundamental aspects of yeast cell homeostasis to improve the performance of a given yeast strain in biotechnological applications.